Pengaruh Pengalaman Audit, Keahlian Audit, Tekanan Ketaatan, Dan Kompleksitas Tugas Terhadap Audit Judgment Auditor (Studi Pada BPK-RI Perwakilan Provinsi Papua Barat) - Billy Johan Herman Ratag; Simson Werimon; Syarifudin (JFRES Journal of Fiscal and Regional Economy Studies, 2021)
This study aims to analyse the influence of audit experience, audit expertise, compliance pressure and complexity of tasks on auditor judgment audits. The sample in this study was an auditor working with the Audit Board of the Republic of Indonesia, representative of West Papua Province. The sample is selected based on purposive sampling method. Data collection was conducted by distributing questionnaires to 42 respondents and returned as many as 32 questionnaires. The data was analyzed using linear regression analysis with SPSS 21. The results of this study show that audit experience affects audit judgment auditors. Audit expertise has no effect on auditors' judgment audits. Compliance pressure affects auditors' judgment audits. The complexity of the task has no effect on the auditor's audit judgment.